Історія одного союзу: взаємини Конрада Мазовецького з Данилом Галицьким у першій половині XIII ст. - Тетерич-Пузьо, А. (Український історичний журнал, 2021)
Мета статті полягає у визначенні ролі, яку відігравав у політиці Конрада Мазовецького його союз із Данилом Галицьким. Методологія дослідження зосереджена на з’ясуванні структури відносин двох князів. Проаналізовано як польські, так й українські джерела. Наукова новизна. Розглянуто основні етапи у взаємовідносинах правителів, переломний момент в яких міг відбутися 1221 р. Підкреслено також значну вагу можновладців, зокрема Пакослава Старого. Висновки. У міжкнязівських відносинах можна виокремити декілька періодів. У 1205–1221 рр. Конрад підтримував політику Лешека Білого, який прагнув підкорити своїм впливам сусідні руські князівства. Наприкінці цього етапу в поглядах цих двох братів на політику щодо Русі почали проявлятися розбіжності. 1221-й рік продемонстрував нові риси в позиції Конрада, який остерігав Данила Галицького про можливі наміри брата щодо запланованого викрадення князя. В умовах посилення ятвязьких, прусських та литовських вторгнень у Мазовецьку землю Конрад відчув потребу у співпраці з руськими князями. 1222–1227 рр. стали періодом зосередженості його на обороні від нападників, тоді як 1228–1235 рр. позначилися тісною співпрацею між Конрадом і Данилом. У 1236–1240 рр. відбулося охолодження у відносинах, але приблизно з 1240 р. й до смерті Конрада в 1247 р. знову спостерігалася стабільна співпраця. У статті також висвітлюється вплив на формування відносин між князями представників можновладців, а саме Пакослава Старого. The alliance with Daniel of Halych played an important role in the policy pursued by Konrad of Mazovia. The purpose of the research. This paper has two objectives. First, to briefly analyse, in the light of sources, the alliance Konrad of Mazovia with Daniel of Halych. Second, to investigate the scope of influence of the members of the nobility e.g. Pakosław the Old in the shaping of relations between the princes. The research methodology. On the basis of an analysis of both Polish and Ukrainian sources, the relationship between Konrad of Mazovia and Daniel of Halych was examined. The scientific novelty. There were discussed the main stages in the relations between Konrad of Mazovia and Daniel of Halych, in which the turning point may be the year of 1221. It was also pointed out the significant role of magnates, such as Pakosław the Old in shaping the relationship between the two princes. Conclusions. In the years 1205–1221 Konrad supported Leszek the White’s policy, who strove to gain influence over the neighbouring Rus principalities. At the end of that period, the brothers began to differ in their views on policy towards Rus. In the year 1221 Konrad’s attitude changed and he warned Daniel of Halych of his brother’s intentions, which possibly concerned the planned kidnapping of the prince. Faced with the intensification of incursions by the Yotvingians, Prussians and Lithuanians into the Land of Mazovia Konrad began to seek cooperation with the princes of Rus. The years 1222–1227 was the time when Konrad of Mazovia focused on the defence against the incursions, while the period from 1228 until ca. 1235 brought about close cooperation between Konrad and Daniel. In the years ca. 1236–1240 a cooling of relations took place, nevertheless, a stable cooperation can be observed in the period dating from ca. 1240 until Konrad’s death in 1247. In the article attention was paid to the role of the members of the nobility played in the shaping of relations between the princes e.g. Pakosław the Old.